I Implementation of Multi-Contract IB Hijrah Rencana Savings Product at Bank Muamalat - Triyatno, Ghazy; Novianti, Irohdatul; Munir, Misbahul; Khasanah, Umrotul (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Abstract This study explains the contract process applied to the iB Hijrah Rencana Savings product offered by Bank Muamalat. This product adheres to Islamic economic principles, is free from riba, and aims to help customers plan their finances according to Sharia law. The objective of this research is to examine how the multi-contract system is implemented in the iB Hijrah Rencana Savings product at Bank Muamalat and to analyze the application of profit-sharing ratios in the product from an Islamic economic perspective. The methodology used in this study is descriptive qualitative, which systematically describes the research subject about the core issues. The study shows that two contracts are applied to the iB Hijrah Rencana Savings product: Mudharabah Muthlaqoh (investment contract) and Tabarru’ (Islamic insurance). The implementation of the profit-sharing ratio is based on a system that refers to the net result of fund management, by Islamic economic principles. This is based on the DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000, ensuring that this product helps society achieve its plans without the concern of funds being mixed with riba. Abstrak Penelitian ini menjelaskan proses akad yang diterapkan pada produk Tabungan iB Hijrah Rencana yang ditawarkan oleh Bank Muamalat. Produk ini menggunakan prinsip-prinsip ekonomi islam yang bebas dari riba dan bertujuan untuk membantu nasabah dalam merencanakan keuangan secara syariah. Penelitian ini bertujuan untuk mengetahui bagaimana penerapan multi akad pada produk Tabungan iB Hijrah Rencana di Bank Muamalat & Menganalisis penerapan nisbah bagi hasil dalam produk tersebut dari perspektif ekonomi Islam. Metodologi yang digunakan dalam penelitian ini adalah deskriptif kualitatif, yang menggambarkan subjek penelitian secara sistematis dengan pokok permasalahan. Penelitian menunjukkan bahwa terdapat duua akad yang ditetapkan pada Tabungan iB Hijrah Rencana, yaitu Mudharabah Muthlaqoh (akad investasi) & Tabarru’ (asuransi syariah). Implementasi nisbah bagi hasil dilakukan berdasarkan sistem bagi hasil yang mengacu pada hasil bersih pengelolaan dana, sesuai dengan perspektif ekonomi islam. Hal ini berpedoman pada Fatwa DSN-MUI No. 02/DSN-MUI/IV/2000, sehingga produk ini diharapkan dapat membantu masyarakat dalam mewujudkan rencana tanpa kekhawatiran dana tercampur dengan riba. Keywords: Profit-sharing; Mudharabah Muthlaqah; Islamic Banking